O uso do Scratch como ferramenta para criação de objetos de aprendizagem no ensino de matemática - Cavalcante, Fernanda Vasconcelos (Universidade Federal do Tocantins, 2023)
This Course Conclusion Work presents a proposal for a Learning Object in game format using the Scratch platform, which is a programming language that uses predefined blocks for the development, creation and animation of games, available online. Our research will be qualitative and bibliographical review, bringing an approach based on the insertion of games and technologies in the teaching of mathematics and computational thinking, working the thought process developed in solving problems. The objects of knowledge to to be taught through the game, were chosen according to the Common National Base Curriculum: Flowchart to determine the parity of a natural number; multiples and divisors of a natural number; Prime and composite numbers. As a result, we developed two games with slightly different proposals, but in a complementary way in terms of content, mixing playful and mathematical challenges, seeking to encourage, motivate and instigate students in learning, offering support to students, both in the school environment and out of it.